Molecular characterization of the gastrula in the turtle Emys orbicularis: an evolutionary perspective on gastrulation. - Coolen, M; Nicolle, D; Plouhinec, J; Gombault, A; Sauka-Spengler, T; Menuet, A; Pieau, C; Mazan, S (Public Library of Science, 2008)
Due to the presence of a blastopore as in amphibians, the turtle has been suggested to exemplify a transition form from an amphibian- to an avian-type gastrulation pattern. In order to test this hypothesis and gain insight into the emergence of the unique characteristics of amniotes during gastrulation, we have performed the first molecular characterization of the gastrula in a reptile, the turtle Emys orbicularis. The study of Brachyury, Lim1, Otx2 and Otx5 expression patterns points to a highly conserved dynamic of expression with amniote model organisms and makes it possible to identify the site of mesoderm internalization, which is a long-standing issue in reptiles. Analysis of Brachyury expression also highlights the presence of two distinct phases, less easily recognizable in model organisms and respectively characterized by an early ring-shaped and a later bilateral symmetrical territory. Systematic comparisons with tetrapod model organisms lead to new insights into the relationships of the blastopore/blastoporal plate system shared by all reptiles, with the blastopore of amphibians and the primitive streak of birds and mammals. The biphasic Brachyury expression pattern is also consistent with recent models of emergence of bilateral symmetry, which raises the question of its evolutionary significance.